2018
DOI: 10.1111/ele.12965
|View full text |Cite
|
Sign up to set email alerts
|

Declining home range area predicts reduced late‐life survival in two wild ungulate populations

Abstract: Demographic senescence is increasingly recognised as an important force shaping the dynamics of wild vertebrate populations. However, our understanding of the processes that underpin these declines in survival and fertility in old age remains limited. Evidence for age-related changes in foraging behaviour and habitat use is emerging from wild vertebrate studies, but the extent to which these are driven by within-individual changes, and the consequences for fitness, remain unclear. Using longitudinal census obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 67 publications
2
57
0
Order By: Relevance
“…A first step for example, could be to quantify exercise and physiological markers during the mating season of polygynous species such as red deer Cervus elephaus or black grouse Lyrurus tetrix, across multiple breeding seasons. This could prove insightful in describing differing rates of senescence between individuals, as indicated by, for instance, declining home range sizes (Froy et al, 2018). With the right techniques, there is huge potential in existing study systems to investigate the impacts of activity on animal senescence.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A first step for example, could be to quantify exercise and physiological markers during the mating season of polygynous species such as red deer Cervus elephaus or black grouse Lyrurus tetrix, across multiple breeding seasons. This could prove insightful in describing differing rates of senescence between individuals, as indicated by, for instance, declining home range sizes (Froy et al, 2018). With the right techniques, there is huge potential in existing study systems to investigate the impacts of activity on animal senescence.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
“…More recently, however, focussed-studies on multiple taxa have shown otherwise (Nussey et al, 2013;Jones et al, 2014). In many species, individuals continue living well beyond their functional peaks (Froy et al, 2018), and often carry on reproducing albeit at a declining rate (Nussey et al, 2013;Jones et al, 2014). Aging in animals can be considered in terms of the decline in the body's performance (functional senescence) or the decline in fertility rate coupled with an increased risk of mortality (demographic senescence).…”
Section: Introduction: Aging In the Wildmentioning
confidence: 99%
“…The metabolic theory of ecology, and related concepts, predicts that the rate of resource uptake, transformation and allocation to processes important for fitness are determined by metabolic rate (Brown, Gillooly, Allen, Savage, & West, ; Brown, Hall, & Sibly, ; Hennemann, ; Humphries & Mccann, ; McNab, ). Home range, the area where animals spend most of their time foraging, resting and reproducing, varies among and within species and can determine individual reproductive success and survival (Burt, ; Froy et al, ). The benefits of large home ranges include better access to resources, food and mates, but large ranges can also generate energetic and predation costs (McNab, ; Tamburello, Côté, & Dulvy, ).…”
Section: Introductionmentioning
confidence: 99%
“…This has been addressed using individual measures of mortality in the following year (Froy et al. ), but comparisons of actuarial and phenotypic senescence estimates from entire adult lifespans have not been attempted before (to our knowledge). We are aware of only two studies that compared the relationship between ageing trajectories of different traits and their relationship to lifespan in the field (Hayward et al.…”
mentioning
confidence: 99%
“…The statistical power of such an analysis is reduced when demographic senescence estimates are based on cohorts within overlapping generations because partially shared environmental histories mean that actuarial senescence estimates are nonindependent. This has been addressed using individual measures of mortality in the following year (Froy et al 2018), but comparisons of actuarial and phenotypic senescence estimates from entire adult lifespans have not been attempted before (to our knowledge). We are aware of only two studies that compared the relationship between ageing trajectories of different traits and their relationship to lifespan in the field (Hayward et al 2015) and in the lab (Briga 2016), reporting heterogeneous associations among ageing trajectories and lifespan, suggesting asynchrony of senescence across different traits.…”
mentioning
confidence: 99%